The Effects of Fatty Acid in Population Related to Body Mass Index - Fivi Melva Diana; Mery Ramadani Ramadani; Najmiatul Fitria (Faculty of Public Health, Andalas University, 2022)
Normal body mass index (BMI) is related to a person's health condition. Consumption of fatty acids is used to keep some problems of BMI abnormalities. The study aimed to assess the relationship between fatty acids and changes in BMI. A systematic review to assess articles related to fatty acids and bmi changes. Database searches are conducted through PubMed. Researchers looked for Omega 3, EPA, DHA, Omega 6, AA as fatty acids. Only articles on humans were included in the study. Articles that are not written in English and without full text are not included. Six articles were included in the study. Clinical trials are used in all included studies. Most studies describe the relationship of fatty acids to pregnancy weight gain in pregnant women. Types of fatty acids that play an essential role are Omega 3, EPA, DHA, ALA, omega 6.Not all fatty acids have a positive impact on humans. There are negative symptoms that need to be addressed, especially outside of BMI.